How Information and Communication Technology Shapes the Influence of Culture on Innovation: A Country-level Analysis. Issue 1 (2nd January 2021) - Saldanha, Terence J.V.; John-Mariadoss, Babu; Wu, Michelle Xiao; Mithas, Sunil
ABSTRACT: Advances in Information and Communication Technology (ICT) and the distributed nature of innovation in a culturally heterogeneous world raise an important question about how ICT and culture jointly influence innovation. We argue that ICT shapes the influence of culture dimensions on national innovation in nuanced ways, depending on the nature of the dimensions. In particular, cultural dimensions that pertain to norms, formality, and structure (e.g., power distance and uncertainty avoidance) are often considered detrimental to innovation, whereas culture dimensions that pertain to the pursuit of goals and achievement (e.g., individualism, masculinity, and long-term orientation) are often considered conducive for innovation. We hypothesize that ICT amplifies the positive effects of individualism, masculinity, and long-term orientation on national innovation—and, attenuates the negative effects of power distance and uncertainty avoidance on national innovation. Our analyses of data on 66 countries from 2007 to 2015 broadly support our hypotheses about ICT amplifying the positive effects of individualism and long-term orientation, as well as our hypotheses about ICT attenuating the negative effects of power distance and uncertainty avoidance on national innovation. The findings suggest that ICT amplifies the effects of culture dimensions related to the pursuit of goals and helps overcome barriers to innovation that arise from a culture's focus on norms, formality, and structure. In turn, these findings can help managers and policy makers to make judicious decisions regarding ICT investments to transcend or leverage the country's cultural characteristics for innovation.